2023
DOI: 10.1039/d2bm01980a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chondroitin sulfate concentration and matrix stiffness on chondrogenic differentiation of mesenchymal stem cells

Abstract: The effect of matrix stiffness and chondroitin sulfate concentration on stem cell chondrogenesis was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A similar study on BMSCs pointed out that stiffness varying can form a suitable network for cartilage differentiation of BMSCs 57 . There is evidence that ADSCs are more likely to differentiate into cartilage than BMSCs; therefore, optimization of hydrogel matrix stiffness favors for MSC chondrogenic differentiation was practicable 58 . Considering decorin was necessary for maintaining fibril structure and mechanical stiffness of tendon and cartilage 59 , 60 , we assumed that application of decorin in gellan gum could serve as viscous substrates to modulate stiffness in a microenvironment, which preserves ADSCs regenerative potential under inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study on BMSCs pointed out that stiffness varying can form a suitable network for cartilage differentiation of BMSCs 57 . There is evidence that ADSCs are more likely to differentiate into cartilage than BMSCs; therefore, optimization of hydrogel matrix stiffness favors for MSC chondrogenic differentiation was practicable 58 . Considering decorin was necessary for maintaining fibril structure and mechanical stiffness of tendon and cartilage 59 , 60 , we assumed that application of decorin in gellan gum could serve as viscous substrates to modulate stiffness in a microenvironment, which preserves ADSCs regenerative potential under inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, ChSMA has also been reported to have an effect. A ChSMA concentration of 6 % was found to be best at promoting chondrogenic differentiation of BMSCs, mainly because such a density is optimal for cell interaction [ 26 ]. Similarly, ChSMA increased Col2a1, Sox9, and Aca by 5.9, 10.97, and 5.56 times on day 14 compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they are often used as scaffolds with RGD peptide for tissue engineering [ 25 ]. Chondroitin Sulfate (ChS) is a natural glycosaminoglycan (≈500 Da), which is an important structural component of cartilage and other connective tissues, with many positive properties, such as promoting chondrogenic differentiation of BMSCs [ 26 ], fostering cartilage generation by balancing chondrocyte metabolism [ 27 , 28 ], promoting anti-inflammation [ 29 ], inhibiting cellular hypertrophy [ 30 ] and enhancing integration with natural cartilage [ 31 ]. However, ChS cannot be used alone to prepare scaffolds because of its good water solubility and inability to form a hydrogel by self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is worth noting that signs of hypertrophic chondrogenic differentiation are commonly observed in cartilage tissue engineering research. For instance, a recent study showed that MSCs cultured in hydrogels composed of gelatin methacryloyl (GelMA) and different concentrations of methacrylated chondroitin sulfate (CSMA) increased COL10 expression across all concentrations [ 39 ]. These findings highlight the challenge of hypertrophic differentiation and emphasize the need to investigate strategies aimed at minimizing or inhibiting this process.…”
Section: Discussionmentioning
confidence: 99%